Impact of early nutrition and feeding route on clinical outcomes of neurocritically ill patients - Young Kyun Choi; Hyun-Jung Kim; Joonghyun Ahn; Jeong-Am Ryu (PLoS ONE, 2023)
Early proper nutritional support is important to critically ill patients. Nutritional support is also associated with clinical outcomes of neurocritically ill patients. We investigate whether early nutrition is associated with clinical outcomes in neurocritically ill patients. This was a retrospective, single-center, observational study including neurosurgical patients who were admitted to the intensive care unit (ICU) from January 2013 to December 2019. Patients who started enteral nutrition or parenteral nutrition within 72 hours after ICU admission were defined as the early nutrition group. The primary endpoint was in-hospital mortality. The secondary endpoint was an infectious complication. Propensity score matching (PSM) and propensity score weighting overlap weights (PSOW) were used to control selection bias and confounding factors. Among 1,353 patients, early nutrition was performed in 384 (28.4%) patients: 152 (11.2%) early enteral nutrition (EEN) and 232 (17.1%) early parenteral nutrition (EPN). In the overall study population, the rate of in-hospital mortality was higher in patients with late nutrition than in those with early nutrition (P<0.001). However, there was no significant difference in in-hospital mortality and infectious complications incidence between the late and the early nutrition groups in the PSM and PSOW adjusted population (all P>0.05). In the overall study population, EEN patients had a low rate of in-hospital mortality and infectious complications compared with those with EPN and late nutrition (P<0.001 and P = 0.001, respectively). In the multivariable analysis of the overall, PSM adjusted, and PSOW adjusted population, there was no significant association between early nutrition and in-hospital mortality and infectious complications (all P>0.05), but EEN was significantly associated with in-hospital mortality and infectious complications (all P<0.05). Eventually, early enteral nutrition may reduce the risk of in-hospital mortality and infectious complications in neurocritically ill patients.